EFFECT OF FMD VACCINATION ON SEMEN GHARACTERISTICS IN HOLSTEIN FRIESIAN BULLS - SAHA, SUJIT; MISHRA, G K; SINGH, R B; SHUKLA, M K; TIWARl, RITESH; SAXENA, S K (The Indian Journal of Animal Reproduction, 2011)
The present study was designed to investigate the effect of Foot and Mouth disease FM □) vaccination on semen production performance and quality parameters on the basis of semen collected from 25 Holstein Friesian bulls maintained at Animal Breeding Centre, Salon, Rae Bareli district of Uttar Pradesh during 2008 and 2009. The results indicated that ejaculate volume and initial motility differ significantly between pre and post vaccination period, while no significant difference was evident with respect to concentration and total sperm output. But for all the parameters maximum deterioration was noticed up to first 10 days post vaccination period. There was a significant change (p<0.05) in the live sperm percentage following vaccination. The percentage of live sperm reduced from 95.23% to 83.19% (10 days after vaccination) and 84.57% (11 -20 days after vaccination), which was significantly improved after 20 days following vaccination (90.18%). Although sperm morphological abnormalities like free normal head, free abnormal head, simple bent tail, mid piece defect etc. were prevalent after vaccination there was no significant difference with respect to percentage of morphologically abnormal sperm between pre and post vaccination period. The study indicates FMD vaccination adversely affects most of the seminal attributes in the initial 10 days but there is no adverse effect on sperm morphology as such.